People's Opium? Religion and Economic Attitudes - Luigi Guiso
Since Max Weber, there has been an active debate on the impact of religion on people's economic attitudes. Much of the existing evidence, however, is based on cross-country studies in which this impact is confounded by differences in other institutional factors. We use the World Values Surveys to identify the relationship between intensity of religious beliefs and economic attitudes, controlling for country fixed effects. We study several economic attitudes toward cooperation, the government, working women, legal rules, thriftiness, and the market economy. We also distinguish across religious denominations, differentiating on whether a religion is dominant in a country. We find that on average, religious beliefs are associated with good' economic attitudes, where good' is defined as conducive to higher per capita income and growth. Yet religious people tend to be more racist and less favorable with respect to working women. These effects differ across religious denominations. Overall, we find that Christian religions are more positively associated with attitudes conducive to economic growth.